Impact of Training Program Upon Nurse-Midwives’ Practices Concerning Third Stage of Labor - jaber, Eman; ali, Rabea (Iraqi National Journal of Nursing Specialties, 2013)
Objective: The aim of this study is to identify the impact of training education program applied on nurse-midwife practice concerning care during third stage of labor in labor room. Examine the relationship between their knowledge regarding practices and some Demographic information’s. Methodology: A quasi-experimental design conducted on non-probability (purposive) sample of fifty two nurse-midwives selected during period from3 th August to 10thNovember 2011. The study is conducted at the Ministry of Health (Baghdad health directorate in Al-Karhk and Al-Risafa sector) in four hospitals. The questionnaire form is consisted of three parts which included demographic data, knowledge concerning practice during third stage of labor, practice checklist. Content validity and reliability of the questionnaire determined through a pilot study, descriptive and inferential statistics are used to analyze the data. Results: Results of the study showed that the highest percentage (44.2%) were in age group of 30-39 years, midwifery school graduate and) 42.3 % (of them had 1-10 years of work experience in midwifery. There were low and moderate means in most items related to the knowledge and practices of nursemidwives regarding third stage of labor in pre-test and assessed as (partial) while there were high mean scores in all items, and assessed Pass in posttest after the implementation of the training education program with high statistical significant . Recommendation: The study recommended that establishment of clinical practice standards according to the WHO, development of continuing education programs; establish a baccalaureate degree program in midwifery.